Proactive prosociality in a cooperatively breeding corvid, the azure-winged magpie (Cyanopica cyana) - Horn, Lisa (Biol Lett, 2016)
One of the contemporary hypotheses concerning the evolution of human altruism is the cooperative breeding hypothesis (CBH) which has recently been tested in non-human primates. Using a similar paradigm, we investigated prosociality in a cooperatively breeding corvid, the azure-winged magpie. We found that the magpies delivered food to their group members at high rates, and unlike other corvids, they did so without any cues provided by others. In two control conditions, the magpies stopped participating over time, indicating that they learned to discriminate prosocial tests from controls. Azure-winged magpies are thus the first birds that experimentally show proactive prosociality. Our findings are in line with the CBH; however, additional corvid species need to be tested in this promising paradigm.